Elevated glycated hemoglobin levels impair blood pressure in children and adolescents with type 1 diabetes mellitus. Issue 1 (December 2016) - Oliveira, Sandra; Cunha Nascimento, Dahan; Tibana, Ramires; Oliveira, Samuel; Sousa Neto, Ivo; Falleiros, Roberta; Miranda, Leonardo; Pedrosa, Hermelinda; Navalta, James; Pereira, Guilherme; Prestes, Jonato
Abstract Background Deregulation of glycemic and glycated hemoglobin (HbA1 ) levels accelerate the progression of cardiovascular complications in type 1 diabetes mellitus (T1DM). The aim of this study was to investigate the association between HbA1 and changes in blood pressure of children and adolescents with T1DM. Methods A total of 60 children and adolescents were recruited and allocated into two groups (prehypertension and control group). Blood pressure and HbA1 were measured by the oscillometric method and high-performance liquid chromatography, respectively. Results The prehypertensive group had (P  < 0.05) higher disease duration, body weight, Z score for body weight, systolic blood pressure (SBP), diastolic blood pressure (DBP) and a higher HbA1 when compared with the control children and adolescents. Multiple regression to predict alterations in DBP from HbA1 adjusted for age, disease duration, and body mass index demonstrated a positive relationship with DBP (P  < 0.05). A 1 % increase in HbA1 was associated with 1.73 mmHg increase in DBP. Conclusions High levels of HbA1 may be associated with increased blood pressure in T1DM. A tight control of HbA1 levels may provide long-term cardiovascular protection in children and adolescents with T1DM.